JA:2021-8. Evaluating the SAY National Clearinghouse. Issue 3 (2nd July 2020) - Fetzer, Linda; Raygor, Andrea; Swenson, Andrea; Yoder, Aaron; Gorucu, Serap
ABSTRACT: Purpose : The purpose of this study was to conduct a formative evaluation to improve the functionality and usability of the Safety in Agriculture for Youth (SAY) Project National Clearinghouse. The SAY Project is a USDA-NIFA grant, and the evaluation is being conducted through a grant through the National Children's Center. Methods : A quarterly SAY Clearinghouse eNews is sent to FFA and 4-H educators in Pennsylvania and Utah as well as people who have signed up for the eNews at the National FFA Convention. Four online surveys were conducted between April 2017 and December 2019 to examine the usability, structure, and available content of the Clearinghouse. This information will be a formative evaluation to make improvements to the Clearinghouse. Results/Findings : The survey results reflect responses from those affiliated with FFA and provides pertinent information about the type and topics of educational resources that they utilize in their program. This type of information is useful when looking at material to include in the SAY Clearinghouse and the promotion. The alignment of the SAY Clearinghouse contents to the AFNR standards was seen positively by the majority of the respondents. Marketing continues to be a challenge for the SAY Clearinghouse because only a small percentage was already familiar with the Clearinghouse. Those individuals familiar with the Clearinghouse learned about it through professional meetings and promotional material. Respondents indicated their likelihood of using SAY materials and positively rated the organization, usability, and range of topics covered by the Clearinghouse. Practical Application : Our overall goal is to reduce the number of injuries and fatalities associated with agricultural operations. SAY National Clearinghouse provides access to agricultural safety and health curriculums and improved safety and health of youth working in agriculture.